Rewiring Mitochondrial Metabolism for CD8+ T Cell Memory Formation and Effective Cancer Immunotherapy - Li, Wenhui; Zhang, Lianjun (Frontiers in Immunology, 2020)
Memory T cells persist for long term to mediate robust recall response upon re-challenging with previous encountered pathogens. The memory T cell pool is highly heterogeneous based on distinct phenotypic, functional and locational properties, and contains discrete subsets which contribute to diverse immune responses. In this mini-review, we will briefly discuss the distinct subsets of memory T cells, and then focus on mitochondria-related metabolic and epigenetic regulations of CD8+ T cell memory formation. In particular, we discuss many aspects of mitochondrial quality control systems (biogenesis, dynamics etc.) in regulating CD8+ T cell fate decision and anti-tumor immunity. Importantly, targeting mitochondrial metabolism to boost T cell memory formation and metabolic fitness might represent an attractive strategy to improve cancer immunotherapy including CAR-T therapy.